Readiness on Online Learning Modality Among Junior High School Teachers of a National High School - Vongtanaboon, V; Hancharoen, W; Homya, S (SAFE-Network, 2024)
One of the modalities used to continue education here in the Philippines during the COVID-19 pandemic is the online learning modality. Online learning will be considered successful if the teachers handling this modality are equipped with appropriate knowledge and the right attitudes and online practices for this kind of teaching. To be regarded as an influential online teacher, their readiness for the modality should be high. This research study describes the of preparedness of high school teacher-respondents of Locloc National High School regarding the use of online learning modality by assessing the knowledge, attitudes, and practices of the thirty-six teacher-respondents focusing on the use of online learning. An online questionnaire was developed and given to each respondent, following strict health guidelines and protocols. Constructed on the research outcomes, Locloc National High School teachers have high knowledge, proper attitudes, and sound practices when it comes to implementing and utilizing the online class modality in their school. Therefore, respondents have a high level of readiness about using online learning modalities for their students. For further improvement of teachers regarding the use of online learning modality, an Online Learning Modality Enhancement Program (Table 20) should be taken into consideration. Other divisions should adapt it for teacher readiness enhancement for online learning modality.